Analisis Manajemen Konflik Peran Ganda Karyawan Perempuan Di Perusahaan Sarana Logistik - Mehanusa, Yuzza Laivo; Rizqi, Maulidyah Amalina (Jurnal Mahasiswa Manajemen, 2023)
Background - The close relationship between the dual roles of women and work productivity often triggers conflict between the two. The emergence of multiple role conflicts often results in employees not being focused at work. Failure to concentrate in doing a job makes the work target mismatch. Objective - The research conducted to analyze double roles and management of conflict that occured on employee of, especially in women. In this research, we are using qualitative method with descriptive approach. Design/Methodology/Approach - The data gathering technic that are used in this research is Semi Structured Interview. Findings - The research found out that application of double roles in Logistik Facilities Company give positive and negative impacts. The positive impact that women employee feels such as they could actually help their own family economy rather than being dependant with their Husband paycheck. In other hand, by working, women employee feel that they could actualize themselves better. With positive outcome that mentioned above, we also found the negative impact such as, women employee feels that it is actually impossible to do both roles at the same time. Research implication - This research can be used as material for consideration for companies with multiple roles. Research Limitations - This study has limitations on factors in the background of multiple roles.